The Influence of Measures Supervision on Performance of the Internal Auditors to Work Motivation as an Intervening Variable (Studies in Riau Province Representative BPKP) - Ayu Januar, Halimah Fahmy; Anugerah, Rita; ', Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine how actions influence the performance of the internalauditor supervision through work motivation. The population of this study is that the internal auditors work in BPKP Representative Office of Riau Province. Total respondents in this study is 74 respondents (64.3%). Methods of data collection in this study is the use of survey method and deliver directly by sending a questionnaire to 115 pieces staffing subsection BPKP Representative Riau Province. The method of data analysis used in this study is to use the technique of path analysis (path analysis) is similar to multiple regression analysis yet done gradually with the help of software SPSS version 17.0. The results of this study indicate that the act of supervision and motivation direct and significant impact on the performance of the internal auditors. The results of this study also showed that motivation does not work mediate the relationship between measures of supervision with the performance of internal auditors.Keyword : Measures Supervision, Work Motivation and Performance of the Internal Auditors